Reaction kinetics of a series of alkenes with ClO and BrO radicals: A theoretical study. Issue 2 (5th October 2020) - Gupta, Parth; Rajakumar, B.
Abstract: Quantum chemical calculations were used to investigate the mechanism and kinetics of the reaction of XO (X = Cl, Br) radicals with linear C2 to C4 alkenes. Two reaction routes, namely, addition and H‐abstraction, were investigated as part of the XO‐radical initiated degradation of these alkenes. Energies and structural parameters were obtained at the CCSD(T)/CBS//M062x/cc‐pVTZ level of theory, and the canonical variational transition state theory with small‐curvature tunneling corrections was used to calculate rate constants at temperatures spanning 200‐3000 K. The addition of the electron‐deficient XO radical onto the olefinic moiety was the major degradation channel, owing to its low barrier heights. Moreover, the H‐abstraction route also played a key role in governing the fate of the alkene in the high‐temperature regime, when compared to the addition routes. The computed branching ratios for various reaction routes further ascertained the relative dominance of the addition and H‐abstraction routes over the studied temperature range. The computed kinetic and thermodynamic parameters can be beneficial towards designing a better chemical kinetic model, relevant for both atmospheric as well as combustion systems. In addition to this, the formed HOCl (or HOBr) can damage the ozone layer and cause ecological imbalance.